Hematuria in Patients with Congenital Coagulation Factor Deficiencies - Nihal Karadaş; Can Balkan; Deniz Yılmaz Karapınar; Yeşim Aydınok; Kaan Kavaklı (Galenos Publishing House, 2022)
Objective: Inherited bleeding disorders are a group of congenital coagulopathies, arising due to protein deficiencies, which affect clotting, platelet function or fibrinolysis. Spontaneous gross hematuria or subclinical microscopic hematuria, which are often detected by chance, are relatively common in patients with coagulopathies. This study aims to evaluate the incidence, the causes and treatment modalities of hematuria in congenital factor deficiencies. Method: Data concerning the type of coagulation defect, the level of deficient factor, age of the patients with hematuria episodes, presence of inhibitor, ongoing treatment modality, the etiology of hematuria, the treatment approach to hematuria, the number of hematuria episodes has been collected from medical records and hemophilia dairies of patients between 1985 and 2015 and confirmed by phone calls. Six hundred twenty nine patients with congenital factor deficiencies followed were evaluated retrospectively. Results: Hematuria was seen in 10.1% of hemophilia A, 15.5% of hemophilia B, 3.8% of von Willebrand's disease patients and 7% of patients with other factor deficiencies. Hematuria was seen in 2 mild, 20 moderate and 29 severe factor VIII and IX deficiencies. In 7 of these patients inhibitor was positive. While no etiological reason for hematuria could be identified in 78% of these patients, 15.3% had nephrolithiasis, 1.7% had post streptococcal acute glomerulonephritis, 3.4% had urinary tract infection and 1.7% had a renal cyst. Conclusion: The study demonstrates that hematuria is relatively common in factor deficiencies, whereas further studies are needed to elucidate the causes and effects on renal function in children with coagulation deficiencies.